Thermomechanical Properties of Jute/Bamboo Cellulose Composite and Its Hybrid Composites: The Effects of Treatment and Fiber Loading - Fui, Kiew Liew; Sinin, Hamdan; Md. Rezaur, Rahman; Mohamad, Rusop (Hindawi Publishing Corporation, 2017)
Jute cellulose composite (JCC), bamboo cellulose composite (BCC), untreated hybrid jute-bamboo fiber composite (UJBC), and jute-bamboo cellulose hybrid biocomposite (JBCC) were fabricated. All cellulose hybrid composites were fabricated with chemical treated jute-bamboo cellulose fiber at 1 : 1 weight ratio and low-density polyethylene (LDPE).The effect of chemical treatment and fiber loading on the thermal, mechanical, and morphological properties of composites was investigated. Treated jute and bamboo cellulose were characterized by Fourier transform infrared spectroscopy (FTIR) to confirm the effectiveness of treatment. All composites were characterized by tensile testing, thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC). Additionally, surface morphology and water absorption test was reported.The FTIR results revealed that jute and bamboo cellulose prepared are identical to commercial cellulose. The tensile strength and Young’s modulus of composites are optimum at 10 weight percentage (wt%) fibers loading. All cellulose composites showed high onset decomposition temperature. At 10 wt% fiber loading, JBCC shows highest activation energy followed by BCC and JCC. Significant reduction in crystallinity index was shown by BCC which reduced by 14%. JBCC shows the lowest water absorption up to 43 times lower compared to UJBC. The significant improved mechanical and morphological properties of treated cellulose hybrid composites are further supported by SEM images.